The Influence of Work Facilities on Employee Performance at the UPT Office of the Goods Quality Testing and Certification Center (BPSMB) of the Industry and Trade Department of South Sulawesi Province - Anindya Maharani Tajuddin; Sitti Nurbaya; Sitti Marhumi (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to determine the Effect of Work Facilities on Employee Performance at the UPT Office of the Goods Quality Testing and Certification Center (BPSMB) Disperindag South Sulawesi Province. The type of research used in this study is quantitative research. The sample in this study was 35 respondents. This study used a simple linear regression analysis and used data sourced from respondents and documentation from the UPT Office of the Goods Quality Testing and Certification Center (BPSMB) Disperindag South Sulawesi Province. Regression test results based on the significant value test (sig) provided that if the sig value <0.05 is obtained the sig value = 0.25 which means <0.05. Thus, it can be concluded that the linear regression equation from the study obtained that work facilities affect employee performance at the UPT Office of the Goods Quality Testing and Certification Center (BPSMB) Disperindag South.